A Roadheader-Assisted Coal Cutter Based on Tensile Failure Mechanism of Coal - Bo Liu; Zhiliu Wang; Wei Xu; Zhiwei Yu; Zhendong Yan; Biao Yao (Geofluids)
This paper proposes a new roadheader-assisted coal cutter (RACC) based on the tensile failure mechanism of coal. An innovative mining method, called the cutting inside and spalling outside mining (CISOM) method, is developed based on this new RACC. The mechanical model is established, and the working mechanism of the new CISOM method is illustrated using a column model and a beam model. The mechanical models reveal that the tensile stress causes greater deflection than compressive stress. The deflection and mining width demonstrates a quadratic relationship. To understand the stratum behaviors and improve mining efficiency, the stability of a working face owned by Jincheng Coal Mining Group in Shanxi is analyzed using UDEC numerical simulation. Numerical results indicate that the optimal values of the parameter are 0.8 m width for the inside cutting and 0.4 m width for the outside spalling at #1305 working face. The newly developed RACC was successfully applied at #1305 working face. The field results showed that the recovery rate of CISOM method is over 90%; i.e., it is improved by 20% in comparison with the traditional method.